2015
DOI: 10.1038/jcbfm.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypothermia Inhibits Systemic and Cerebral Complement Activation in a Swine Model of Cardiac Arrest

Ping Gong,
g Zhao,
Rong Hua
et al.

Abstract: Complement activation has been implicated in ischemia/reperfusion injury. This study aimed to determine whether mild hypothermia (HT) inhibits systemic and cerebral complement activation after resuscitation from cardiac arrest. Sixteen minipigs resuscitated from 8 minutes of untreated ventricular fibrillation were randomized into two groups: HT group (n=8), treated with HT (33°C) for 12 hours; and normothermia group (n=8), treated similarly as HT group except for cooling. Blood samples were collected at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
6
17
0
Order By: Relevance
“…We expect the classical and the alternative pathway to contribute to the formation of common pathway components in post‐cardiac arrest syndrome; however, the extent is still unknown. A previous animal study has demonstrated that all 3 initiating pathways were activated after cardiac arrest, but from the LP Gong et al only included MBL. Thus, the complement system may play an important role in exacerbating the damage after cardiac arrest, and therefore, studies to target complement system proteins should be of future interest.…”
Section: Discussionmentioning
confidence: 99%
“…We expect the classical and the alternative pathway to contribute to the formation of common pathway components in post‐cardiac arrest syndrome; however, the extent is still unknown. A previous animal study has demonstrated that all 3 initiating pathways were activated after cardiac arrest, but from the LP Gong et al only included MBL. Thus, the complement system may play an important role in exacerbating the damage after cardiac arrest, and therefore, studies to target complement system proteins should be of future interest.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial activation is closely coupled to leukocyte activation and the systemic inflammatory response, why the different development in cytokine levels over time and increased levels of elastase in the aged animals is consistent with the increased endothelial activation also observed in these animals. Several studies have shown leukocyte activation and increased cytokine levels in patients after CA, however, without investigating the effect of age . Two clinical studies have established an association between plasma levels of IL‐6 and elastase and poor outcome in post‐CA patients .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that hypothermic therapy can effectively protect multiple injuries of the brain and spinal cord [7]. In a swine model of CA, previous studies have shown that mild hypothermia has protective effects against ischemic damage in the brain and demonstrated that reduction of oxidative stress, enhancement of antioxidant enzyme expressions [8], inhibition of brain edema, proinflammatory cytokine [9], and complement activation [10] are underlying mechanisms for cerebral neuroprotection after applying hypothermia.…”
Section: Introductionmentioning
confidence: 99%